Behavioral aspects of phlebotomine sand flies associated with a case of cutaneous leishmaniasis in Atlántico, northern Colombia (2020)
After the first autochthonous case of cutaneous leishmaniasis was reported in the Atlántico department in the Caribbean region of Colombia, entomological sampling was conducted in the specific areas where the infection might have occurred. CDC traps were installed inside and outside dwellings in the peri-urban and rural areas of a settlement in the municipality of Luruaco. Sampling was performed during the night with protected human bait, and phlebotomine sand flies were actively sampled from potential diurnal resting sites within dwellings. Ten species of the genus Lutzomyia were identified; Lutzomyia evansi was the dominant species (78%) in the rural and peri-urban areas as well as in the different sampled habitats, followed by Lutzomyia panamensis and Lutzomyia gomezi. There was a 100% household infestation by Lu. evansi, and its indoor mean abundance was 13.3 sand flies/CDC trap/night. The indoor mean abundance of Lu. panamensis and Lu. gomezi was only 0.9 and 0.8 sand flies/CDC trap/night, respectively. Female Lu. evansi were collected with protected human bait, mostly in the peridomestic area, with sustained activity during the night and a slight increase in the activity from 19:00 to 23:00 hours. Of the total sand flies captured in the diurnal resting sites, 73.1% were collected from the walls of bedrooms and corresponded to Lu. evansi, Lutzomyia cayennensis cayennensis, and Lutzomyia trinidadensis. Owing to their vectorial importance, the species on which entomological surveillance should be focused are Lu. evansi, Lu. panamensis, and Lu. gomezi. The biting and resting behavior reported in this study will help guide vector prevention and the control of leishmaniasis within the study area.